2006
DOI: 10.1055/s-2005-921203
|View full text |Cite
|
Sign up to set email alerts
|

Video Capsule Endoscopy in Small-bowel Malignancy: A Multicenter Belgian Study

Abstract: Tumors of the small bowel remain a rare condition. Video capsule endoscopy is able to detect tumors undiagnosed by classical procedures in about 1.6% of cases and has an impact on the therapy in 55% of the tumor cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
50
1
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(59 citation statements)
references
References 13 publications
6
50
1
1
Order By: Relevance
“…The mean age of patients with small bowel tumors was 47.1 years, which was lessened by the patients with benign polyps such as Peutz-Jeghers polyps, and the mean age of patients with GISTs/leiomyomata, lymphomas, or adenocarcinomas was above 50 years. Although the mean age of the patients with small bowel tumors was above 60 years in several CE studies [4][5][6][7][8][9][10], the mean age of those patients with small bowel tumors was 53 years in a Japanese DBE study [17], which is comparable with our results. The disagreement is not thought to be because of racial difference but because of the difference of the mean age between patients who received CE and patients who underwent DBE.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The mean age of patients with small bowel tumors was 47.1 years, which was lessened by the patients with benign polyps such as Peutz-Jeghers polyps, and the mean age of patients with GISTs/leiomyomata, lymphomas, or adenocarcinomas was above 50 years. Although the mean age of the patients with small bowel tumors was above 60 years in several CE studies [4][5][6][7][8][9][10], the mean age of those patients with small bowel tumors was 53 years in a Japanese DBE study [17], which is comparable with our results. The disagreement is not thought to be because of racial difference but because of the difference of the mean age between patients who received CE and patients who underwent DBE.…”
Section: Discussionsupporting
confidence: 89%
“…In the past, the diagnosis of small bowel tumors was made mainly through SBFT, abdominal CT, or even laparotomy; however, more accurate diagnosis for small bowel tumors became possible after the development of CE and DBE. The frequency of small bowel tumors in patients who receive CE has been reported to be 1.6-8.9% [4][5][6][7][8][9][10], while the frequency in patients who receive DBE is 10.0, 11.5 and 13.9% according to studies performed in Germany, Portugal, and Japan, respectively [15][16][17]. This difference is because DBE is usually performed to confirm abnormal findings that have been detected by other imaging studies, including CE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SB mass lesions are responsible for OGIB in up to 10% of patients [44][45][46][47][48] . Early clinical studies of CE have reported a frequency of SB tumors ranging between 6% and 9% [49][50][51][52][53][54] . This has led to an idea that CE doubled the rate of diagnosing SB tumors.…”
Section: Small Bowel Tumors and Polypsmentioning
confidence: 99%
“…(Ciresi & Scholten, 1995;DiSario et al, 1994;Lewis, 1994;Lewis et al, 2005;Kariv & Arber 2003). Early clinical studies of CE have reported a frequency of SB tumors ranging between 6% and 9% (Bailey et al,2006;Cobrin et al,2006;de Franchis et al,2004;Estevez et al,2007;Schwartz &Barkin,2007;Urbain et al,2006). This has led to an idea that CE doubled the rate of diagnosing SB tumors.…”
Section: Small Bowel Tumors and Polypsmentioning
confidence: 99%